5V high-voltage positive electrode material, precursor material and manufacturing method
By using nickel manganese lithium positive electrode material and using multiple process routes to synthesize, the existing lithium battery voltage platform and specific capacity are solved, and the high energy density and safety requirements are met.
Patent Information
- Application Number
- CN202411569314.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The voltage platform and specific capacity of existing lithium batteries are insufficient, making it difficult to meet the high energy density and safety needs of electric vehicles.
Nickel manganese phosphate (NMP) is used as the positive electrode material and synthesized through different process routes such as solid phase method, liquid phase method, gel method, hydrothermal method to achieve high purity, low impurity, and uniform particles.
A high voltage platform (up to 5.1V) and high specific capacity (up to 860Wh/Kg) are realized, which significantly improves the cycle life and thermal stability of the battery and reduces costs.
Smart Images

Figure CN119542378A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a 5V high-voltage positive electrode material and a precursor material, namely, an olivine nickel manganese lithium phosphate positive electrode material and a method for preparing the material. Background Art
[0002] With the national policy support for new energy electric vehicles and the market application of electric vehicles, higher requirements have been placed on lithium batteries, the power source of electric vehicles. The most important thing is that the voltage platform and specific capacity of lithium batteries must adapt to the development requirements of electric vehicles. The specific energy of traditional lithium iron phosphate monomer batteries is only 110-120Wh / kg. After being combined into a battery pack, the energy density of the battery system is less than 100Wh / kg. Although the ternary material has a certain improvement over lithium iron phosphate in specific energy, it cannot meet the needs of power batteries in terms of thermal stability, safety, cycle life, processing difficulty and cost. Therefore, how to increase battery capacity, improve safety performance, increase cycle life, reduce costs, etc.; and then increase the cruising range of electric vehicles while ensuring safety and optimizing the best cost performance has always been a dilemma in the industry. The patent of this invention aims to seek new lithium battery positive electrode materials, mainly to improve the voltage platform, improve thermal stability, and at the same time greatly improve the cycle life, reduce costs, increase specific energy, promote a significant increase in the cruising range of electric vehicles, and obtain more ideal power battery performance. Summary of the invention
[0003] In view of the shortcomings of the performance and technology of existing lithium batteries, especially lithium iron phosphate and ternary materials, the technical problem to be solved by the present invention is to provide a phosphate battery material with a high voltage platform and specific capacity. The theoretical voltage platform of the nickel manganese lithium phosphate of the present invention can reach 5.1V, while the voltage platform of lithium iron phosphate is only 3.2V; the voltage platform of the three elements 811 is also only 3.5V; in terms of specific capacity, nickel manganese lithium phosphate can reach 860WH / Kg, and lithium iron phosphate is only 540Wh / Kg, which is nearly 50% higher than that of lithium iron phosphate. The invention of this patent can be used to batch produce the material through solid phase method, gel method, liquid phase method, and hydrothermal method. The raw materials are easy to obtain, the process can be realized in a variety of ways, and the temperature and humidity of the environment during the production process are far less demanding than the high nickel ternary requirements. Nickel manganese phosphate lithium positive electrode battery material can achieve high purity, low impurities, small and uniform particle size. The synthesized nickel manganese phosphate lithium battery has high gram capacity, good rate discharge performance, excellent high and low temperature performance, and the number of cycles is equivalent to that of lithium iron phosphate. The voltage platform is far superior to lithium iron phosphate and ternary, and the comprehensive electrical performance is far superior to ternary.
[0004] The object of the present invention is achieved by: a method for manufacturing a nickel manganese lithium phosphate positive electrode or precursor material; 1. Solid phase method Precursor: Manganese source, nickel source, phosphorus source and doping element raw materials are added in proportion according to the stoichiometric ratio, fully dispersed by sand grinding in a sand mill, and spray dried after reaching the designed particle size requirement. The dried material is sintered and dehydrated in a high-temperature sintering furnace for phase change to obtain nickel manganese phosphate material.
[0005] Positive electrode: manganese source, nickel source, lithium source, carbon source, phosphorus source and doping element raw materials are added in proportion to the stoichiometric ratio, fully dispersed by sand grinding in a sand mill, and spray dried after reaching the designed particle size requirement. The dried material is sintered in an inert gas protection furnace for pyrolysis reaction and phase change to obtain a carbon-coated nickel manganese lithium phosphate positive electrode material.
[0006] 2. Liquid phase method / gel method: Precursor: fully dissolve the manganese source and nickel source in a certain concentration of phosphorus source aqueous solution in advance, filter, add alkaline substances to adjust the pH value for precipitation and crystallization; filter the slurry to obtain a filter cake and wash it with pure water; dry and sinter the filter cake to obtain an NMP precursor substance.
[0007] Positive electrode: After the components of NMP-based precursor materials are determined, carbon source, lithium source and element doping materials are added in proportion according to the stoichiometric ratio. The materials are fully dispersed by sand grinding in a sand mill. After reaching the designed particle size requirements, they are spray dried. The dried materials are sintered in an inert gas protection furnace for pyrolysis reaction and phase change to obtain carbon-coated nickel manganese lithium phosphate positive electrode materials.
[0008] 3. Hydrothermal method or critical hydrothermal method NMP positive electrode material: Soluble manganese source, nickel source and phosphorus source are fully dissolved and filtered in advance according to the stoichiometric ratio to obtain a clean solution. In a hydrothermal kettle, a hydrothermal reaction is carried out at a certain pressure and temperature. After a period of OSTWALD reaction, the material is filtered to obtain a filter cake. The filter cake is dried, preliminarily crushed, graded, a certain amount of carbon source and lithium source are added for fine-tuning mixing, sintered under inert gas protection, and gas-powdered to obtain NMP positive electrode material.
[0009] Positive electrode: Soluble manganese source, nickel source, lithium source, carbon source, phosphorus source and doping elements are fully dissolved and filtered in advance according to the stoichiometric ratio to obtain a clean solution. In a hydrothermal kettle, a hydrothermal reaction is carried out at a certain pressure and temperature. After a period of OSTWALD reaction, the material is filtered to obtain a filter cake. The filter cake is dried, preliminarily crushed, graded, a certain amount of carbon source and lithium source are added for fine-tuning mixing, sintered under inert gas protection, and gas-powdered to obtain LNMP positive electrode material.
[0010] The SEM morphology of the precursor NMP obtained by the method provided by the present invention is plate-like or layered, and its appearance is light yellow or yellow-green; the SEM morphology of the prepared positive electrode material LNMP is a relatively rounded spherical olivine structure material. The product has high dispersibility and fluidity, and the vibration ratio can reach 0.95g / cm 3 The impurity content is extremely low, S≤50ppm, Na≤50ppm, K≤50ppm, heavy metals such as Cu, Pb, Cd, Cr≤10ppm; Ca, Mg≤50ppm, magnetic substances≤1ppm; the voltage platform is about 5.25V, and the 0.1C gram capacity is about 160mAh / g.
[0011] The nickel manganese lithium phosphate product produced by the present invention is easy to control in terms of the molar ratio of nickel, manganese and lithium elements, and the ratio of the three elements can be accurately controlled and adjusted arbitrarily; the impurity content is extremely low, the product has a high degree of dispersibility and fluidity, and the vibration ratio is above 0.95; the particle size distribution is in a relatively narrow range, wherein D 50 The particle size is stable at 0.5-2.0μm. SEM electron microscope shows that the product morphology is plate-like or flaky, with extremely high compaction density, and XRD also shows that the obtained nickel manganese lithium phosphate product is a pure phase olivine structure product. Through the buckle battery simulation test made of the material, the voltage platform is basically around 5.2V, and the 0.1C capacity reaches 160-161.5mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0013] Attached Figure 1 This is the XDR (radiological diffraction) diagram of the nickel manganese lithium phosphate prepared in Example 1 of the present invention.
[0014] Attached Figure 2 This is the XDR (radiological diffraction) diagram of the nickel manganese lithium phosphate prepared in Example 2 of the present invention.
[0015] Attached Figure 3 This is the XDR (radiological diffraction) diagram of the nickel manganese lithium phosphate prepared in Example 3 of the present invention.
[0016] Attached Figure 4 This is the XDR (radiological diffraction) diagram of the nickel manganese lithium phosphate prepared in Example 4 of the present invention.
[0017] Attached Figure 5 This is a scanning electron microscope image (SEM image) of the nickel manganese phosphate obtained in Example 1 of the present invention.
[0018] Attached Figure 6 This is a scanning electron microscope image (SEM image) of the nickel manganese phosphate obtained in Example 2 of the present invention.
[0019] Attached Figure 7This is a scanning electron microscope image (SEM image) of the nickel manganese phosphate obtained in Example 3 of the present invention.
[0020] Attached Figure 8 This is a scanning electron microscope image (SEM image) of the nickel manganese phosphate obtained in Example 4 of the present invention.
[0021] Attached Fig. 9 This is the laser particle size distribution diagram of nickel manganese lithium phosphate obtained in Example 1 of the present invention.
[0022] Attached Fig.10 This is the laser particle size distribution diagram of nickel manganese lithium phosphate obtained in Example 2 of the present invention.
[0023] Attached Fig.11 This is the laser particle size distribution diagram of nickel manganese lithium phosphate obtained in Example 3 of the present invention.
[0024] Attached Fig.12 This is the laser particle size distribution diagram of nickel manganese lithium phosphate obtained in Example 4 of the present invention.
[0025] Attached Fig.13 This is the nickel manganese lithium phosphate obtained in Example 1 of the present invention (electrical performance curve).
[0026] Attached Fig.14 This is the nickel manganese lithium phosphate obtained in Example 2 of the present invention (electrical performance curve).
[0027] Attached Fig.15 This is the nickel manganese lithium phosphate obtained in Example 3 of the present invention (electrical performance curve).
[0028] Attached Fig.16 This is the nickel manganese lithium phosphate obtained in Example 4 of the present invention (electrical performance curve). DETAILED DESCRIPTION
[0029] The implementation process of the present invention is as follows: manganese, nickel source, lithium source, carbon source, phosphorus source are set according to different process routes such as solid phase method, liquid phase method, hydrothermal method, and nickel-manganese molar ratio, and then synthesize LNMP or NMP products, where the molecular formula of the positive electrode material is Li a Ni b Mn d M e PO4 / C, in which the manganese valence is divalent; The precursor is nickel manganese phosphate (NMP), and the general structural formula is Ni b Mn d M e PO4, where the nickel-manganese element compound valence can be divalent or trivalent, or conductive agents such as CNT (carbon nanotubes) or GO (graphene oxide) can be added in advance during synthesis to improve the material performance, optimizing and improving some electrical properties of the precursor itself.
[0030] A nickel manganese phosphate active material with an olivine structure, the general structural formula is Ni b Mn d M e PO4, b is 0.1-0.95, d is 0.05-0.9, and e is: 0≥e≤0.5; M is a doping element, and M is selected from one or more combinations of Fe, Al, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, nickel, Sc, Cr, Cu, Zn, Be, La, Mg, N, and S. The valence of nickel and manganese elements can be divalent or trivalent.
[0031] In some embodiments, the structural formula Ni b Mn d M e In PO4, b is 0.5 to 0.95, d is 0.2 to 0.9, and e is 0.05 to 0.5.
[0032] In some embodiments, the structural formula Ni b Mn d M e In PO4, b is 0.5 to 0.8, d is 0.2 to 0.5, and e is 0.05 to 0.15.
[0033] In some embodiments, the structural formula Ni b Mn d M e In PO4, b is 0.5, 0.6, 0.7, or 0.8; d is 0.2, 0.3, 0.4, or 0.5; e is 0, 0.05, 0.1, or 0.15.
[0034] In some embodiments, the structural formula Ni b Mn d M e In PO4, b is 0.8, d is 0.2, and e is 0.05, 0.1, or 0.15; or b is 0.7, d is 0.3, and e is 0.05, 0.1, or 0.15; or b is 0.6, d is 0.4, and e is 0.05, 0.1, or 0.15; or b is 0.5, d is 0.5, and e is 0.05, 0.1, or 0.15.
[0035] In some implementation cases, the present invention prepares the nickel manganese phosphate active material with the structural formula Ni 0.8 Mn 0.2 PO4, Ni 0.8 Mn 0.2 M 0.05 PO4, Ni0.8 Mn 0.2 M 0.1 PO4, Ni 0.8 Mn 0.2 M 0.15 PO4, Ni 0.7 Mn 0.3 PO4, Ni 0.7 Mn 0.3 M 0.05 PO4, Ni 0.7 Mn 0.3 M 0.1 PO4, Ni 0.7 Mn 0.3 M 0.15 PO4, Ni 0.6 Mn 0.4 PO4, Ni 0.6 Mn 0.4 M 0.05 PO4, Ni 0.6 Mn 0.4 M 0.1 PO4, Ni 0.6 Mn 0.4 M 0.15 PO4, Ni 0.5 Mn 0.5 PO4, Ni 0.5 Mn 0.5 M 0.05 PO4, Ni 0.5 Mn 0.5 M 0.1 PO4, Ni 0.5 Mn 0.5 M 0.15 PO4, M is any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg.
[0036] The manganese source used in the synthesis process of the above materials is selected from one or more combinations of metallic manganese, manganese monoxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese citrate, manganese acetate, manganese oxalate, manganese sulfate, manganese nitrate, and manganese chloride.
[0037] The nickel source is selected from one or more combinations of nickel metal, nickel hydroxide, nickel sulfate, nickel oxalate, nickel carbonate, nickel nitrate and nickel chloride.
[0038] The raw material of the doping element M is selected from one or more combinations of sulfates, phosphates, nitrates, chlorides, oxalates, acetates, and carbonates of any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg.
[0039] The particle size of the nickel manganese phosphate active material having an olivine structure is D 50 0.5-2.0 μm, more preferably D 50 1.0-1.6 μm, more preferably D 50 1.2-1.55μm.
[0040] In view of the above technical solution, the present invention also provides a carbon-coated nickel manganese lithium phosphate composite material, the structural formula of the carbon-coated nickel manganese lithium phosphate composite material includes the structural formula of the nickel manganese phosphate active material, and the structural formula of the carbon-coated nickel manganese lithium phosphate composite material is Li a Ni b Mn d M e PO4 / C, a is 0.01~1.05, and the sum of (a+b+d+e) and PO4 3- The ratio of the root molar value is 0.90-1.05, and the values of b, d, and e are taken from Ni b Mn d M e The value in the PO4 general formula.
[0041] As a preferred embodiment, a is 1.025 to 1.035, and more preferably any one of 1.025, 1.026, 1.027, 1.028, 1.029, 1.030, 1.031, 1.032, 1.033, 1.034, or 1.035; When 0<a<1.025, nickel manganese phosphate pre-embedded with lithium is obtained.
[0042] The carbon source in the carbon-coated composite material is selected from one or more combinations of organic carbon, artificial or natural graphite, graphene, carbon nanotubes or Super P, acetylene black or other conductive carbons; the carbon content is 0.1-10%. The introduction of carbon in the present invention is to increase conductivity, but it is not the only means. Low carbon can be used in combination with other conductive agents; high carbon content will lead to poor processing performance, difficult to control moisture, and low gram capacity.
[0043] The present invention also provides a 5V high voltage platform phosphate positive electrode material, which is a combination of any one or more of the nickel manganese phosphate active material with an olivine structure or the carbon-coated nickel manganese lithium phosphate composite material.
[0044] Another technical solution of the present invention is to set different process routes such as solid phase method, liquid phase method, hydrothermal method and nickel-manganese molar ratio of manganese, manganese, lithium, carbon and phosphorus to synthesize LNMP or NMP products, wherein the molecular formula of the positive electrode material is Li a Ni b Mn d M e PO4 / C, where the manganese valence is divalent, the specific technical scheme is as follows: A method for preparing a nickel manganese phosphate active material having an olivine structure: a manganese source, a nickel source, a phosphorus source and a doping element raw material are added in proportion according to the element stoichiometric ratio in the above structural formula, fully sand-ground and dispersed in a sand mill, spray-dried after reaching the particle size requirement, and the dried material is sintered and dehydrated in a high-temperature sintering furnace for phase change to obtain a nickel manganese phosphate material; Alternatively, the manganese source, nickel source, lithium source, carbon source, phosphorus source and doping element raw materials are added in proportion to the element stoichiometric ratio in the above structural formula, fully dispersed by sand grinding in a sand mill, spray dried after reaching the particle size requirement, and the dried material is sintered and dehydrated in a high-temperature sintering furnace for phase change to obtain a carbon-coated nickel manganese lithium phosphate positive electrode material.
[0045] The manganese source is selected from one or more combinations of metallic manganese, manganese monoxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese citrate, manganese acetate, manganese oxalate, manganese sulfate, manganese nitrate, and manganese chloride; The nickel source is selected from one or more combinations of nickel metal, nickel hydroxide, nickel sulfate, nickel oxalate, nickel carbonate, nickel nitrate, and nickel chloride; The lithium source is selected from one or more combinations of lithium carbonate, lithium bicarbonate, lithium sulfate, lithium phosphate, lithium oxalate and lithium hydroxide; The phosphorus source is selected from a combination of one or more of ammonium phosphate, lithium phosphate, sodium phosphate, phosphoric acid, and hypophosphorous acid; The raw material of the doping element M is selected from one or more combinations of sulfates, phosphates, nitrates, chlorides, oxalates, acetates, and carbonates of any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg; The carbon source is selected from one or more combinations of organic carbon, artificial or natural graphite, graphene, carbon nanotubes or Super P, acetylene black or other conductive carbons.
[0046] In the above steps, the manganese source, nickel source, phosphorus source and doping element raw materials are mixed, or the manganese source, nickel source, lithium source, carbon source, phosphorus source and doping element raw materials are mixed and water is added to form a slurry, a surfactant is added, and the temperature is raised to 90-120° C. to react for 2-4 hours. After the reaction, the nickel manganese lithium phosphate filter cake obtained by filtering is dried and ball milled.
[0047] The surfactant is a mixture of allyl polyethylene glycol, pyridine, polyvinyl pyridine, PVP and the like in a mass ratio of 4:2-3:0.5-2.
[0048] Carbon source and lithium source are added during the ball milling process, so that the product structure contains Li a Ni b Mn d M e PO4 / C, the molar amount of lithium is 0.01-1.05, and the carbon content is 0.1-10%.
[0049] In the process of preparing nickel manganese phosphate material, the doping element M is selectively added, and the addition amount of each raw material is controlled according to the atomic ratio of each raw material in the doping element M of the manganese source, nickel source and phosphorus source, so that the structure of the nickel manganese phosphate active material is Ni b Mn d M e PO4, b is 0.1-0.95, d is 0.05-0.9, and e is 0≤e≤0.5; M is a doping element, and M is selected from one or more combinations of Fe, Al, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, Mg, N, S or Al.
[0050] In some specific embodiments, the structure of the nickel manganese phosphate active material prepared is Ni 0.8 Mn 0.2 PO4、Ni 0.7 Mn 0.3 PO4、Ni 0.6 Mn 0.4 PO4 or Ni 0.5 Mn 0.5 PO4, M is any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg.
[0051] The particle size requirement is D of a single group of materials. 50 The size of the nanostructured material is preferably within 400 nm, more preferably within 200 nm, and even more preferably within 100 nm. The nanostructured material has good gram capacity and rate characteristics, and the cycle performance is even better.
[0052] The sand grinding particle size is controlled at D50 of 0.2~0.8μm; The particle size of the product obtained after the spray drying is recommended to be 15-25 μm, and more preferably 10-15 μm; The carbon coating sintering temperature is: the low-temperature coke removal section temperature is set to 250-650°C, more preferably 400-500°C, and the high-temperature phase change section temperature is 680-800°C, more preferably 700-790°C.
[0053] A nickel manganese phosphate active material with an olivine structure is prepared by one of the methods to obtain a nickel manganese phosphate positive electrode material or a carbon-coated nickel manganese phosphate positive electrode material. The active material has a 5V high voltage platform as a phosphate positive electrode material.
[0054] A 5V high voltage platform phosphate positive electrode material, prepared by one of the methods to obtain a nickel manganese phosphate positive electrode material or a carbon-coated nickel manganese phosphate positive electrode material, the structural formula of the nickel manganese phosphate positive electrode material is Ni b Mn d M e PO4, b is 0.1-0.95, d is 0.05-0.9, and e is 0≤e≤0.5; M is a doping element, and M is selected from one or more combinations of Fe, Al, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, Mg, N, S or Al.
[0055] The structural formula Ni b Mn d M e In PO4, b is 0.5 to 0.95, d is 0.2 to 0.9, and e is 0.05 to 0.5.
[0056] In the preferred embodiment, the general structural formula Ni b Mn d M e In PO4, b is 0.5 to 0.8, d is 0.2 to 0.5, and e is 0 to 0.15.
[0057] A further preferred structural formula is Ni b Mn d M e In PO4, b is 0.5, 0.6, 0.7, or 0.8; d is 0.2, 0.3, 0.4, or 0.5; e is 0, 0.05, 0.1, or 0.15.
[0058] A further preferred structural formula is Ni b Mn d M eIn PO4, b is 0.8, d is 0.2, and e is 0.05, 0.1, or 0.15; or b is 0.7, d is 0.3, and e is 0.05, 0.1, or 0.15; or b is 0.6, d is 0.4, and e is 0.05, 0.1, or 0.15; or b is 0.5, d is 0.5, and e is 0, 0.05, 0.1, or 0.15.
[0059] In a further preferred general structural formula, the structural formula of the nickel manganese phosphate active material is Ni 0.8 Mn 0.2 M 0.05 PO4, Ni 0.8 Mn 0.2 M 0.1 PO4, Ni 0.8 Mn 0.2 M 0.15 PO4, Ni 0.7 Mn 0.3 M 0.05 PO4, Ni 0.7 Mn 0.3 M 0.1 PO4, Ni 0.7 Mn 0.3 M 0.15 PO4, Ni 0.6 Mn 0.4 M 0.05 PO4, Ni 0.6 Mn 0.4 M 0.1 PO4, Ni 0.6 Mn 0.4 M 0.15 PO4, Ni 0.5 Mn 0.5 M 0.05 PO4, Ni 0.5 Mn 0.5 M 0.1 PO4, Ni 0.5 Mn 0.5 M 0.15 PO4, M is any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg.
[0060] The structural formula of the carbon-coated nickel manganese lithium phosphate positive electrode material prepared by one of the methods is Li a Ni b Mn d M e PO4 / C, a is 0.01~1.05, and the sum of (a+b+d+e) and PO4 3- The ratio of root molar values is 0.90-1.05.
[0061] The a is 1.025 to 1.035, and more preferably any one of 1.025, 1.026, 1.027, 1.028, 1.029, 1.030, 1.031, 1.032, 1.033, 1.034, or 1.035; When 0<a<1.025, nickel manganese phosphate pre-embedded with lithium is obtained.
[0062] A second method for preparing a nickel manganese phosphate active material with an olivine structure, comprising fully dissolving a manganese source and a nickel source in a phosphorus source aqueous solution of a certain concentration, filtering, adding an alkaline substance to adjust the pH value to 2-9, and performing precipitation crystallization; filtering the crystallized slurry to obtain a filter cake and fully washing the filter cake with pure water; drying and sintering the filter cake to obtain a nickel manganese phosphate active material with an olivine structure; Alternatively, a carbon source, a lithium source and a doping element are added to the nickel manganese phosphate active material, and after grinding and dispersion, the particle size is spray-dried, and the dried material is sintered to obtain a carbon-coated nickel manganese lithium phosphate positive electrode material with an olivine structure.
[0063] In the preparation of nickel manganese phosphate active material, the amount of each raw material added is according to the structural formula Ni b Mn d M e PO4, b is 0.1~0.95, d is 0.05~0.9, e is 0≤e≤0.5 and is reasonably adjusted. Or according to the general structural formula Li a Ni b Mn d M e PO4 / C, a is 0.01~1.05, and the sum of (a+b+d+e) and PO4 3- The ratio of root molar values is 0.90-1.05 for contract adjustment.
[0064] The alkaline substance is selected from any one of sodium hydroxide, lithium hydroxide, ammonia water, cesium carbonate, sodium carbonate, sodium bicarbonate, sodium methoxide, potassium ethoxide and potassium tert-butoxide.
[0065] An alkaline substance is added to adjust the pH value to 1-5, preferably 1.5-5, and more preferably 3.5-4.5.
[0066] The crystallization of the material occurs in an environment where the elements can effectively form crystals, avoiding the situation where some of the necessary elements in the material remain in an ionic state, and at the same time obtaining a material with a purer crystal phase and higher crystallinity.
[0067] The precipitation crystallization time is 1-48 h, preferably 12-16 h, more preferably 8-10 h, and most preferably 4-6 h.
[0068] The manganese source is selected from one or more combinations of metallic manganese, manganese monoxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese citrate, manganese acetate, manganese oxalate, manganese sulfate, manganese nitrate, and manganese chloride; The nickel source is selected from one or more combinations of nickel metal, nickel hydroxide, nickel sulfate, nickel oxalate, nickel carbonate, nickel nitrate, and nickel chloride; The lithium source is selected from one or more combinations of lithium carbonate, lithium bicarbonate, lithium sulfate, lithium phosphate, lithium oxalate and lithium hydroxide; The phosphorus source is selected from a combination of one or more of ammonium phosphate, lithium phosphate, sodium phosphate, phosphoric acid, and hypophosphorous acid; The raw material of the doping element M is selected from one or more combinations of sulfates, phosphates, nitrates, chlorides, oxalates, acetates, and carbonates of any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg; The carbon source is selected from one or more combinations of organic carbon, artificial or natural graphite, graphene, carbon nanotubes or Super P, acetylene black or other conductive carbons.
[0069] The sand grinding particle size is controlled at D50 of 0.2~0.8μm; The particle size of the product obtained after the spray drying is recommended to be 15-25 μm, and more preferably 10-15 μm; The carbon coating sintering temperature is: the low-temperature coke removal section temperature is set to 250-650°C, more preferably 400-500°C, and the high-temperature phase change section temperature is 680-800°C, more preferably 700-790°C.
[0070] A nickel manganese phosphate active material with an olivine structure is prepared by the second method to obtain a nickel manganese phosphate positive electrode material or a carbon-coated nickel manganese phosphate positive electrode material. The active material has a 5V high voltage platform as a phosphate positive electrode material.
[0071] A 5V high voltage platform phosphate positive electrode material, prepared by the second method to obtain a nickel manganese phosphate positive electrode material or a carbon-coated nickel manganese phosphate positive electrode material, the structural formula of the nickel manganese phosphate positive electrode material is Ni b Mn d M e PO4, b is 0.1-0.95, d is 0.05-0.9, and e is 0≤e≤0.5 (the M is a doping element, and M is selected from one or more combinations of Fe, Al, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, Mg, N, and S.
[0072] The structural formula Ni b Mn d M e In PO4, b is 0.5 to 0.95, d is 0.2 to 0.9, and e is 0.05 to 0.5.
[0073] In the preferred embodiment, the general structural formula Ni b Mn d M e In PO4, b is 0.5 to 0.8, d is 0.2 to 0.5, and e is 0 to 0.15.
[0074] A further preferred structural formula is Ni b Mn d M e In PO4, b is 0.5, 0.6, 0.7, or 0.8; d is 0.2, 0.3, 0.4, or 0.5; and e is 0, 0.05, 0.1, or 0.15.
[0075] A further preferred structural formula is Ni b Mn d M e In PO4, b is 0.8, d is 0.2, and e is 0.05, 0.1, or 0.15; or b is 0.7, d is 0.3, and e is 0.05, 0.1, or 0.15; or b is 0.6, d is 0.4, and e is 0.05, 0.1, or 0.15; or b is 0.5, d is 0.5, and e is 0, 0.05, 0.1, or 0.15.
[0076] In a further preferred general structural formula, the structural formula of the nickel manganese phosphate active material is Ni 0.8 Mn 0.2 M 0.05 PO4, Ni 0.8 Mn 0.2 M 0.1 PO4, Ni 0.8 Mn 0.2 M 0.15 PO4, Ni 0.7 Mn 0.3 M 0.05 PO4, Ni 0.7 Mn 0.3 M 0.1 PO4, Ni 0.7 Mn 0.3 M 0.15 PO4, Ni 0.6 Mn 0.4 M 0.05 PO4, Ni 0.6 Mn 0.4 M 0.1 PO4, Ni0.6 Mn 0.4 M 0.15 PO4, Ni 0.5 Mn 0.5 M 0.05 PO4, Ni 0.5 Mn 0.5 M 0.1 PO4, Ni 0.5 Mn 0.5 M 0.15 PO4, M is any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg.
[0077] The structural formula of the carbon-coated nickel manganese lithium phosphate positive electrode material prepared by the second method is Li a Ni b Mn d M e PO4 / C, a is 0.01~1.05, and the sum of (a+b+d+e) and PO4 3- The ratio of root molar values is 0.90-1.05.
[0078] The a is 1.025 to 1.035, and more preferably any one of 1.025, 1.026, 1.027, 1.028, 1.029, 1.030, 1.031, 1.032, 1.033, 1.034, or 1.035; When 0<a<1.025, nickel manganese phosphate pre-embedded with lithium is obtained.
[0079] Another technical solution of the present invention is to provide a third method for preparing a nickel manganese phosphate active material having an olivine structure, wherein a soluble manganese source, a nickel source, and a phosphorus source are fully dissolved and filtered according to a stoichiometric ratio to obtain a clean solution, and a hydrothermal reaction is carried out in a hydrothermal kettle at a certain pressure and temperature. After a period of hydrothermal reaction, the discharged material is filtered to obtain a filter cake, and the filter cake is dried and sintered to obtain a nickel manganese phosphate active material having an olivine structure; Alternatively, a soluble manganese source, a nickel source, a lithium source, a phosphorus source, a carbon source and doping elements are fully dissolved and filtered according to a stoichiometric ratio to obtain a clean solution, and a hydrothermal reaction is carried out in a hydrothermal kettle at a certain pressure and temperature. After a period of hydrothermal reaction, the material is filtered to obtain a filter cake, and the filter cake is dried and sintered to obtain a carbon-coated nickel manganese phosphate active material with an olivine structure.
[0080] The stoichiometry is based on the general structural formula Ni b Mn d M ePO4, b is 0.1~0.95, d is 0.05~0.9, 0≤e≤0.5, make reasonable adjustments. Or according to Li a Ni b Mn d M e PO4 / C, a is 0.01~1.05, and the sum of (a+b+d+e) and PO4 3- The ratio of the root molar values is adjusted appropriately to 0.90-1.05.
[0081] The hydrothermal reaction temperature is 120-200°C, and the hydrothermal reaction pressure is 5-20MPa. The sintering temperature is 400-600°C, and more preferably 450-500°C. It is recommended to analyze why the temperature and pressure conditions of the hydrothermal reaction can achieve the active product, and what kind of environment the hydrothermal reaction provides for each raw material. What are the effects of excessive hydrothermal temperature and pressure on the structural characteristics of the product.
[0082] The manganese source is selected from one or more combinations of metallic manganese, manganese monoxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese citrate, manganese acetate, manganese oxalate, manganese sulfate, manganese nitrate, and manganese chloride; The nickel source is selected from one or more combinations of nickel metal, nickel hydroxide, nickel sulfate, nickel oxalate, nickel carbonate, nickel nitrate, and nickel chloride; The lithium source is selected from one or more combinations of lithium carbonate, lithium bicarbonate, lithium sulfate, lithium phosphate, lithium oxalate and lithium hydroxide; The phosphorus source is selected from a combination of one or more of ammonium phosphate, lithium phosphate, sodium phosphate, phosphoric acid, and hypophosphorous acid; The raw material of the doping element M is selected from one or more combinations of sulfates, phosphates, nitrates, chlorides, oxalates, acetates, and carbonates of any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg; The carbon source is selected from one or more combinations of organic carbon, artificial or natural graphite, graphene, carbon nanotubes or Super P, acetylene black or other conductive carbons.
[0083] A nickel manganese phosphate active material with an olivine structure is prepared by the third method to obtain a nickel manganese phosphate positive electrode material or a carbon-coated nickel manganese phosphate positive electrode material. The active material has a 5V high voltage platform as a phosphate positive electrode material.
[0084] A 5V high voltage platform phosphate positive electrode material, prepared by the third method to obtain a nickel manganese phosphate positive electrode material or a carbon-coated nickel manganese phosphate positive electrode material, the structural formula of the nickel manganese phosphate positive electrode material is Ni b Mnd M e PO4, b is 0.1-0.95, d is 0.05-0.9, 0≤e≤0.5; M is a doping element, and M is selected from one or more combinations of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, Mg, N, S or Al.
[0085] The structural formula Ni b Mn d M e In PO4, b is 0.5 to 0.95, d is 0.2 to 0.9, and e is 0.05 to 0.5.
[0086] In the preferred embodiment, the general structural formula Ni b Mn d M e In PO4, b is 0.5 to 0.8, d is 0.2 to 0.5, and e is 0 to 0.15.
[0087] A further preferred structural formula is Ni b Mn d M e In PO4, b is 0.5, 0.6, 0.7, or 0.8; d is 0.2, 0.3, 0.4, or 0.5; and e is 0, 0.05, 0.1, or 0.15.
[0088] A further preferred structural formula is Ni b Mn d M e In PO4, b is 0.8, d is 0.2, and e is 0.05, 0.1, or 0.15; or b is 0.7, d is 0.3, and e is 0.05, 0.1, or 0.15; or b is 0.6, d is 0.4, and e is 0.05, 0.1, or 0.15; or b is 0.5, d is 0.5, and e is 0, 0.05, 0.1, or 0.15.
[0089] In a further preferred general structural formula, the structural formula of the nickel manganese phosphate active material is Ni 0.8 Mn 0.2 M 0.05 PO4, Ni 0.8 Mn 0.2 M 0.1 PO4, Ni 0.8 Mn 0.2 M 0.15 PO4, Ni 0.7 Mn 0.3 M 0.05 PO4, Ni 0.7 Mn 0.3 M0.1 PO4, Ni 0.7 Mn 0.3 M 0.15 PO4, Ni 0.6 Mn 0.4 M 0.05 PO4, Ni 0.6 Mn 0.4 M 0.1 PO4, Ni 0.6 Mn 0.4 M 0.15 PO4, Ni 0.5 Mn 0.5 M 0.05 PO4, Ni 0.5 Mn 0.5 M 0.1 PO4, Ni 0.5 Mn 0.5 M 0.15 PO4, M is any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg.
[0090] The structural formula of the carbon-coated nickel manganese lithium phosphate positive electrode material prepared by the third method is Li a Ni b Mn d M e PO4 / C, a is 0.01~1.05, and the sum of (a+b+d+e) and PO4 3- The ratio of root molar values is 0.90-1.05.
[0091] The a is 1.025 to 1.035, and more preferably any one of 1.025, 1.026, 1.027, 1.028, 1.029, 1.030, 1.031, 1.032, 1.033, 1.034, or 1.035; When 0<a<1.025, nickel manganese phosphate pre-embedded with lithium is obtained.
[0092] A 5V high-voltage lithium battery pole piece of the present invention comprises a battery pole piece made of the positive electrode material, that is, a carbon-coated nickel manganese lithium phosphate composite positive electrode material pole piece, wherein the positive electrode material component contains 1-100wt% of a carbon-coated nickel manganese lithium phosphate positive electrode material, and the carbon-coated nickel manganese lithium phosphate positive electrode material has a structural formula of Li a Ni b Mn d M e PO4 / C, a is 0.01~1.05, and the sum of (a+b+d+e) and PO4 3- The ratio of root molar values is 0.90-1.05.
[0093] The a is 1.025 to 1.035, and more preferably any one of 1.025, 1.026, 1.027, 1.028, 1.029, 1.030, 1.031, 1.032, 1.033, 1.034, or 1.035; When 0<a<1.025, nickel manganese phosphate pre-embedded with lithium is obtained.
[0094] The positive electrode material composition contains 1-90wt% of carbon-coated nickel manganese lithium phosphate positive electrode material, preferably the positive electrode material composition contains 10-80wt% of carbon-coated nickel manganese lithium phosphate positive electrode material, preferably the positive electrode material composition contains 20-70wt% of carbon-coated nickel manganese lithium phosphate positive electrode material, preferably the positive electrode material composition contains 30-70wt% of carbon-coated nickel manganese lithium phosphate positive electrode material, preferably the positive electrode material composition contains 30-60wt% of carbon-coated nickel manganese lithium phosphate positive electrode material.
[0095] When the carbon-coated nickel manganese lithium phosphate positive electrode material is less than 100%, it also contains other positive electrode materials, and the other positive electrode materials are selected from any one of lithium cobalt oxide, lithium manganese oxide, nickel manganese lithium phosphate, nickel cobalt manganese, and nickel cobalt manganese ternary polymer materials. In some implementation cases, the present invention provides a 5V high-voltage lithium battery, which includes the corresponding stacked sheets, square aluminum shells, cylindrical windings or other lithium batteries of different shapes and structures made of the 5V high-voltage lithium battery pole pieces, and the lithium battery contains at least one lithium element electrolyte solution.
[0096] The manganese sources described in the present invention, namely elemental manganese, manganese monoxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese citrate, manganese acetate, manganese oxalate, manganese sulfate, manganese nitrate and manganese chloride are all materials of analytical grade or above.
[0097] The nickel sources, namely elemental nickel, nickel hydroxide, nickel sulfate, nickel oxalate, nickel carbonate, nickel nitrate and nickel chloride, are all analytically pure or higher materials.
[0098] The lithium sources, namely lithium carbonate, lithium bicarbonate, lithium sulfate, lithium phosphate, lithium oxalate and lithium hydroxide, are all analytically pure or higher materials.
[0099] The phosphorus sources, namely phosphorus pentoxide, phosphoric acid and hypophosphorous acid, are all analytically pure or higher materials.
[0100] The raw materials of the doping element M, i.e., sulfates, phosphates, nitrates, chlorides, oxalates, acetates, and carbonates of any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg, are all analytically pure or higher.
[0101] The carbon sources, namely organic carbon, artificial or natural graphite, graphene, carbon nanotubes or Super P, acetylene black or other conductive carbons are all analytically pure or higher.
[0102] In the surfactant of the present invention, the surfactant is a mixture of allyl polyethylene glycol, polyvinyl pyridine and PVP.
[0103] Example 1 1. First weigh 2000g of 16% dilute phosphoric acid solution with a Baume degree of 10.5-11°Bé; 178.5g of analytical grade nickel hydroxide, 0.5g of battery-grade titanium oxide, 64g of battery-grade manganese tetraoxide, 57.9g of lithium carbonate, and 15g of 5% graphene oxide slurry, add them to the reactor in sequence, stir thoroughly for 10 minutes, and then add 15g of high-efficiency surfactant (a mixture of allyl polyethylene glycol, polyvinyl pyridine, and PVP in a mass ratio of 4:3:2); raise the temperature to about 90°C, stir, and react fully for 2-4 hours; 2. Filter the solution from the previous step through a plate and frame filter to obtain a nickel manganese lithium phosphate filter cake, which is ready for use; 3. Dry the damp product in a CT hot air circulation oven at 140°C for 2.5 hours, crush the obtained dry product, screen it, and then determine the components. According to the component content, the mass of the organic carbon source and the optimized lithium amount are calculated by the stoichiometric ratio and the carbon content in LNMP; the organic carbon sources glucose and PEG6000 are added in amounts of 20.33g and 12.4g respectively; the amount of lithium carbonate added is 1.59g; 4. Control the solid-liquid ratio of the previous material to 40-45% and the viscosity to 4000-5000 Pa.S. Stir thoroughly in the batching tank for 10 minutes, pump into the sand mill for sand grinding, and control the particle size D 50 =500nm, the main engine speed is set to 1200r / min; 5. Spray dry the sand-grinding slurry; 6. The material in step 5 is sintered in a N2 gas inert furnace. The low-temperature sintering temperature is controlled at 450°C, the high-temperature sintering temperature is controlled at 760°C, and the temperature rise rate of each stage is controlled at 3°C / min.
[0104] 7. Grind the material in step 6 by air flow to a particle size of D 50 The particle size was controlled at 1.27 μm, and after screening, grading and packaging, 260.7 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) finished product was obtained: LiMn 0.4 Ni 0.6PO4 / C (nickel-manganese molar ratio is 6:4), this step material can be tested for carbon content, compaction, and electrical properties. (Li is only measured in mass percentage in the material, usually 4.2-4.5%) 8. Mix the LNMP / C powder material, PVDF and conductive carbon black in the 7th step in a mass ratio of 95:5:5, and then use N-methylpyrrolidone dispersant to disperse and adjust the slurry. To ensure uniform dispersion, a double planetary agitator can be used for strong dispersion. The latter half of the dispersed slurry is evenly coated on the carbon-coated aluminum foil by a coating machine and dried; 9. The dried semi-finished electrode pieces are extruded twice by a roller machine; the extruded electrode pieces are cut by a punching machine to obtain φ32mm circular electrode pieces for use as positive electrode pieces for button cell assembly.
[0105] 10. Assemble the electrodes into 2032 button batteries according to the requirements of the simulated battery for electrical performance measurement.
[0106] The test results of the finished product are shown in the following table:
[0107] Embodiment 2: 1. Weigh 300g of battery-grade nickel sulfate and 300g of 85% industrial phosphoric acid, dissolve them in 2500g of pure water at about 80℃, then add 140.7g of battery-grade manganese sulfate monohydrate, 90.2g of battery-grade lithium hydroxide, and 20g of 5% graphene oxide slurry, add them to the reactor in sequence, stir thoroughly for 10 minutes, and then add 15g of high-efficiency surfactant (ethylene propyl polyethylene glycol: polyvinyl pyridine: PVP=4:3:2); raise the temperature to about 95℃, stir, and react fully for 60min; adjust the pH value to 3.5~4.5 with ammonia water and continue to keep warm for 120min.
[0108] 2. Filter the solution from the previous step through a plate and frame filter or a PP barrel type precision filter to obtain a nickel manganese phosphate filter cake, and keep it for later use.
[0109] 3. Dry the damp NMP product in a CT hot air circulation oven at 140°C for 2.5 hours, crush the dry product, screen it, and determine its components. According to the component content, the mass of the organic carbon source and the optimized lithium amount are calculated by the stoichiometric ratio and the carbon content in LNMP. The added amounts of organic carbon sources glucose and PEG6000 are 23.5g and 15.7g respectively; the added amount of lithium carbonate is 2.37g.
[0110] 4. Control the solid-liquid ratio of the previous material to 40-45% and the viscosity to 4000-5000 Pa·S. Stir thoroughly in the batching tank for 15 minutes, pump into the sand mill for sand grinding, and control the particle size D 50=400nm, the main engine speed is set to 900r / min.
[0111] 5. Spray dry the sand-grinding slurry.
[0112] 6. The material in step 5 is sintered in an inert furnace under the protection of high-purity N2 gas. The low-temperature sintering temperature is controlled at 450°C, the high-temperature sintering temperature is controlled at 730°C, and the temperature rise rate of each stage is controlled at 3°C / min.
[0113] 7. Grind the material in step 6 by air flow to a particle size of D 50 The particle size was controlled at 1.34 μm, and after screening, grading and packaging, 410.9 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) finished product was obtained: LiMn 0.2 Ni 0.8 PO4 (nickel-manganese molar ratio is 8:2). In this step, the material can be tested for carbon content, compaction, and electrical properties.
[0114] 8. Mix the LNMP / C powder material, PVDF and conductive carbon black in the 7th step in a ratio of 95:5:5, and then disperse and slurry with N-methylpyrrolidone dispersant. To ensure uniform dispersion, a double planetary agitator can be used for strong dispersion. The latter half of the dispersed slurry is evenly coated on the carbon-coated aluminum foil by a coating machine and dried.
[0115] 9. The dried semi-finished electrode pieces are extruded twice by a roller machine; the extruded electrode pieces are cut by a punching machine to obtain φ32mm circular electrode pieces for use as positive electrode pieces for button cell assembly.
[0116] 10. Assemble the electrodes into 2032 button batteries according to the requirements of the simulated battery for electrical performance measurement.
[0117] The test results of the finished product are shown in the following table:
[0118] Example 3 1. Weigh 550g of analytical grade nickelous nitrate and 332g of 85% industrial phosphoric acid, dissolve them in 2000g of pure water at about 75℃, then add 212.5g of battery grade manganese nitrate, 71.5g of battery grade lithium hydroxide and 7g of CNT, add them into a 5000L hydrothermal reactor in sequence, set the temperature to 180±2℃, and control the pressure in the reactor at 1.35±0.1Mpa; fully react for 240min.
[0119] 2. Filter the slurry from the previous step through a plate and frame filter to obtain a nickel manganese lithium phosphate filter cake, i.e., LNMP wet product for standby use.
[0120] 3. Dry the damp LNMP in a CT hot air circulation oven at 160°C for 2.5 hours, crush the dry material, screen it, and determine the components. According to the component content, the mass of the organic carbon source and the optimized lithium amount are calculated by the stoichiometric ratio and the carbon content in LNMP. The added amounts of organic carbon sources glucose and PEG6000 are 22.7g and 12.5g, respectively; the added amount of lithium carbonate is 1.89g.
[0121] 4. Control the solid-liquid ratio of the previous material to 40-45% and the viscosity to 4000-5000 Pa.S. Stir thoroughly in the batching tank for 15 minutes, pump into the sand mill for sand grinding, and control the particle size D 50 =600nm, the main engine speed is set to 900r / min.
[0122] 5. Spray dry the sand-grinding slurry.
[0123] 6. The material in step 5 is sintered in an inert furnace under the protection of high-purity N2 gas. The low-temperature sintering temperature is controlled at 450°C, the high-temperature sintering temperature is controlled at 770°C, and the temperature rise rate of each stage is controlled at 3°C / min.
[0124] 7. Grind the material in step 6 by air flow to a particle size of D 50 The particle size was controlled at 1.51 μm, and after screening, grading and packaging, 410.9 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) was obtained: LiMn 0.3 Ni 0.7 PO4 (nickel-manganese molar ratio is 7:3). In this step, the material can be tested for carbon content, compaction, and electrical properties.
[0125] 8. Mix the LNMP / C powder material, PVDF and conductive carbon black in the 7th step in a ratio of 95:5:5, and then disperse and slurry with N-methylpyrrolidone dispersant. To ensure uniform dispersion, a double planetary agitator can be used for strong dispersion. The latter half of the dispersed slurry is evenly coated on the carbon-coated aluminum foil by a coating machine and dried.
[0126] 9. The dried semi-finished electrode pieces are extruded twice by a roller machine; the extruded electrode pieces are cut by a punching machine to obtain φ32mm circular electrode pieces for use as positive electrode pieces for button cell assembly.
[0127] 10. Assemble the electrodes into 2032 button batteries according to the requirements of the simulated battery for electrical performance measurement.
[0128] The test results of the finished product are shown in the following table:
[0129] Example 4 1. Weigh 350 g of analytical pure nickel oxalate monohydrate, 555.5 g of ammonium dihydrogen phosphate, 1500 g of pure water, 98.5 g of battery-grade manganese carbonate, 66.5 g of battery-grade lithium carbonate, 15 g of 5% graphene oxide slurry, 25 g of glucose, 23 g of PEG6000, and 10 g of high-efficiency surfactant (allyl polyethylene glycol: fatty alcohol and ethylene oxide condensate: ether phosphate = 4:3:2), add them into a 3000L beaker in sequence, and stir thoroughly for 10 minutes to disperse.
[0130] 2. Control the solid-liquid ratio of the previous material at 40-45%, and the viscosity at 4000-5000 Pa.S. The pure water volume can be controlled and pumped into the sand mill for sand grinding to control the particle size D 50 =300nm, the main engine speed is set to 1500r / min.
[0131] 3. Spray dry the sand-grinding slurry.
[0132] 4. The materials in step 5 are sintered in an inert furnace under the protection of high-purity N2 gas. The low-temperature sintering temperature is controlled at 450°C, the high-temperature sintering temperature is controlled at 750°C, and the temperature rise rate of each stage is controlled at 3°C / min.
[0133] 5. Grind the material from step 4 by air flow to a particle size of D 50 The particle size was controlled at 1.55 μm, and after screening, grading and packaging, 267.4 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) finished product was obtained: LiMn 0.5 Ni 0.5 PO4 (nickel-manganese molar ratio is 5:5). In this step, the material can be tested for carbon content, compaction, and electrical properties.
[0134] 6. Mix the LNMP / C powder material, PVDF and conductive carbon black in the 5th step in a ratio of 95:5:5, and then disperse and adjust the slurry with N-methylpyrrolidone dispersant. To ensure uniform dispersion, a double planetary agitator can be used for strong dispersion. The latter half of the dispersed slurry is evenly coated on the carbon-coated aluminum foil by a coating machine and dried.
[0135] 7. The dried semi-finished electrode pieces are extruded twice by a roller machine; the extruded electrode pieces are cut by a punching machine to obtain φ32mm circular electrode pieces for use as positive electrode pieces for button cell assembly.
[0136] 8. Assemble the electrodes into 2032 button batteries according to the requirements of the simulated battery for electrical performance measurement.
[0137] The test results of the finished product are shown in the following table:
[0138] Example 5 The method and steps are the same as those in Example 1, except that 0.3 g of magnesium nitrate and 0.3 g of zinc nitrate are added to the raw materials in step 1. After all the raw materials are mixed, high-energy ball milling is performed at 1200 r / min for 5 h. Finally, 327.58 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) product is obtained: LiMn 0.4 Ni 0.6 Mg 0.01 Zn 0.07 PO4 / C (nickel-manganese molar ratio is 6:4).
[0139] The test results of the finished product are shown in the following table:
[0140] Example 6 The method and steps are the same as those in Example 1, except that 0.5 g of vanadium pentoxide and 0.5 g of beryllium chloride are added to the raw materials in step 1. After all the raw materials are mixed, they are subjected to high-energy ball milling at 1200 r / min for 5 h. Finally, 371.99 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) product is obtained: LiMn 0.4 Ni 0.6 V 0.022 Be 0.012 PO4 / C (nickel-manganese molar ratio is 6:4).
[0141] The test results of the finished product are shown in the following table:
[0142] Example 7 The method and steps are the same as those in Example 1, except that 1.5 g of cobalt chloride is added to the raw materials in step 1. After all the raw materials are mixed, they are subjected to high-energy ball milling at 1200 r / min for 5 h. Finally, 376.82 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) product is obtained: LiMn 0.4 Ni 0.6 Co 0.15 PO4 / C (nickel-manganese molar ratio is 6:4).
[0143] The test results of the finished product are shown in the following table:
[0144] Example 8 The method and steps are the same as those in Example 2, except that 0.8 g of copper sulfate is added to the raw materials in step 1. After all the raw materials are mixed, the pH value is adjusted to 2.0-3.0, and finally 413.65 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) finished product is obtained: LiMn 0.2 Ni 0.8 Cu 0.05 PO4 / C (nickel-manganese molar ratio is 8:2) The test results of the finished product are shown in the following table:
[0145] Example 9 The method and steps are the same as those in Example 2, except that lithium carbonate is added to 143.7 g in step 3, and finally 412.1 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) product is obtained: Li 1.025 Mn 0.2 Ni 0.8 PO4 / C (nickel-manganese molar ratio is 8:2).
[0146] The test results of the finished product are shown in the following table:
[0147] Example 10 The method and steps are the same as those in Example 3, except that lithium carbonate is added to 136.54 g in step 3, and finally 381.32 g of carbon-coated lithium nickel manganese phosphate (LNMP / C) product is obtained: Li 1.035 Mn 0.3 Ni 0.7 PO4 / C (nickel-manganese molar ratio is 7:3).
[0148] The test results of the finished product are shown in the following table:
[0149] Embodiment 11 The method and steps are the same as those in Example 4, except that in step 8, the obtained LNMP / C powder material, 622 ternary, PVDF, and conductive carbon black are mixed in a ratio of 80:10:5:5, and after dispersion and slurry adjustment, a double planetary agitator is used to disperse the slurry vigorously to ensure uniform dispersion. The semi-dispersed slurry is evenly coated on the carbon-coated aluminum foil by a coating machine and dried.
[0150] The test results of the finished product are shown in the following table:
[0151] Example 12 The method and steps are the same as those in Example 4, except that in step 8, the obtained LNMP / C powder material, lithium manganate, PVDF, and conductive carbon black are mixed in a ratio of 75:15:5:5, and after dispersion and slurry adjustment, a double planetary agitator is used to perform strong dispersion to ensure uniform dispersion. The semi-dispersed slurry is evenly coated on a carbon-coated aluminum foil by a coating machine and dried.
[0152] The test results of the finished product are shown in the following table:
[0153] It should also be noted that the various specific technical features described in the above specific embodiments are willing to be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe various possible combinations one by one.
[0154] The above-mentioned embodiments are only preferred embodiments for fully illustrating the present invention. The scope is not limited thereto. Any equivalent substitution or modification made by those skilled in the art based on the present invention shall be deemed to be within the scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a 5V high voltage positive electrode material, characterized in that: The manganese source, nickel source, phosphorus source and doping element raw materials are mixed and water is added to form a slurry, and the temperature is raised to 90-120°C for reaction for 2-4 hours. The nickel manganese lithium phosphate filter cake obtained by filtration after the reaction is fully sand-milled and dispersed in a sand mill. A carbon source and a lithium source are added during the ball milling process so that the product structure formula Li a Ni b Mn d M e PO4, after the sand grinding particle size is controlled to D50 of 0.2~0.8μm, spray drying is performed, and the dried material is sintered and dehydrated in a high-temperature sintering furnace for phase change to obtain nickel manganese phosphate material; Alternatively, a manganese source, a nickel source, a lithium source, a carbon source, a phosphorus source and a doping element raw material are mixed and water is added to form a slurry, and the temperature is raised to 90-120° C. to react for 2-4 hours. After the reaction, a nickel manganese lithium phosphate filter cake is obtained by filtration, and the filter cake is dried and fully dispersed by sand milling in a sand mill. During the ball milling process, a carbon source and a lithium source are added so that the product structure formula Li a Ni b Mn d M e PO4, after the sand grinding particle size is controlled to D50 of 0.2-0.8 μm, spray drying is performed, and the dried material is sintered and dehydrated in a high-temperature sintering furnace for phase change to obtain a carbon-coated nickel manganese lithium phosphate positive electrode material; Nickel manganese phosphate active material with olivine structure, the general structural formula is Ni b Mn d M e PO4, wherein b is 0.8, d is 0.2, and e is 0≤e≤0.5; or b is 0.7, d is 0.3, and e is 0≤e≤0.5; or b is 0.6, d is 0.4, and e is 0≤e≤0.5; or b is 0.5, d is 0.5, and e is 0≤e≤0.5; M is a doping element, and M is selected from one or more combinations of Fe, Al, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, Mg, N, or S.
2. The method for preparing a 5V high voltage positive electrode material according to claim 1, characterized in that: The manganese source is selected from one or more combinations of metallic manganese, manganese monoxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese citrate, manganese acetate, manganese oxalate, manganese sulfate, manganese nitrate, and manganese chloride; The nickel source is selected from one or more combinations of nickel metal, nickel hydroxide, nickel sulfate, nickel oxalate, nickel carbonate, nickel nitrate, and nickel chloride; The lithium source is selected from one or more combinations of lithium carbonate, lithium bicarbonate, lithium sulfate, lithium phosphate, lithium oxalate and lithium hydroxide; The phosphorus source is selected from one or more combinations of ammonium phosphate, lithium phosphate, sodium phosphate, phosphoric acid, and hypophosphorous acid; The raw material of the doping element M is selected from one or more combinations of sulfates, phosphates, nitrates, chlorides, oxalates, acetates, and carbonates of any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg; The carbon source is selected from one or more combinations of organic carbon, artificial or natural graphite, graphene, carbon nanotubes or Super P, acetylene black or other conductive carbon, PEG, and glucose; The surfactant is any one of allyl polyethylene glycol, polyvinyl pyridine and PVP, in a mixture with a mass ratio of 4:2-3:0.5-2.
3. The method for preparing a 5V high voltage positive electrode material according to claim 2, characterized in that: The molar amount of lithium is 0.01-1.05, the carbon content is 0.1-10%, the solid-liquid ratio is adjusted to 40-45%, the viscosity is controlled at 4000-5000 Pa·s, and the powder is ground to a particle size of D50 of 200-800 nm and then spray-dried; The particle size of the product obtained after the spray drying is 15-25 μm, more preferably 10-15 μm.
4. The method for preparing a 5V high voltage positive electrode material according to claim 1, characterized in that: The particle size requirement is D of a single group of materials. 50 Within 200 nm, more preferably within 100 nm; The carbon coating sintering temperature is: the low-temperature coke removal section temperature is set to 250-650°C, more preferably 400-500°C, and the high-temperature phase change section temperature is 680-800°C, more preferably 700-790°C.
5. A method for preparing a 5V high voltage positive electrode material, characterized in that: After mixing the manganese source, nickel source and phosphorus source, or after mixing the manganese source, nickel source, lithium source, carbon source, phosphorus source and doping element raw materials, water is added to make a slurry, a surfactant is added, the temperature is raised to 90-120° C. to react for 1-4 hours, an alkaline substance is added to adjust the pH value to 1-5, and then the temperature is kept warm for 2-4 hours to obtain a nickel manganese lithium phosphate filter cake after the reaction; The crystallized slurry is filtered to obtain a filter cake, and the filter cake is fully washed with pure water; the filter cake is dried and sintered to obtain a nickel manganese phosphate active material having an olivine structure; Alternatively, a carbon source, a lithium source and a doping element are added to the nickel manganese phosphate active material, the particles are spray dried after grinding and dispersion, and the dried material is sintered to obtain a carbon-coated nickel manganese lithium phosphate positive electrode material having an olivine structure; Nickel manganese phosphate active material with olivine structure, the general structural formula is Ni b Mn d M e PO4, wherein b is 0.8, d is 0.2, and e is 0≤e≤0.5; or b is 0.7, d is 0.3, and e is 0≤e≤0.5; or b is 0.6, d is 0.4, and e is 0≤e≤0.5; or b is 0.5, d is 0.5, and e is 0≤e≤0.5; M is a doping element, and M is selected from one or more combinations of Fe, Al, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, Mg, N, or S.
6. The method for preparing a 5V high voltage positive electrode material according to claim 5, characterized in that: The alkaline substance is selected from any one of sodium hydroxide, lithium hydroxide, ammonia water, cesium carbonate, sodium carbonate, sodium bicarbonate, sodium methoxide, potassium ethoxide, and potassium tert-butoxide, and the alkaline substance is added to adjust the pH value to 1.5-5, preferably 3.5-4.5; The surfactant is a mixture of allyl polyethylene glycol, polyvinyl pyridine and PVP in a mass ratio of 4:2-3:0.5-2. After drying, carbon source and lithium source are added to make the product structure Li a Ni b Mn d M e PO4 / C, the molar amount of lithium is 0.01-1.05, the carbon content is 0.1-10%, the solid-liquid ratio is adjusted to 40-45%, the viscosity is controlled at 4000-5000 Pa·s, and the particle size D50 is ground to 200-800 nm and then spray-dried; The ball mill speed is 800-1200r / min; The particle size of the product obtained after the spray drying is 15-25 μm, more preferably 10-15 μm; the sintering temperature is 400-600°C, more preferably 450°C-500°C.
7. The method for preparing a 5V high voltage positive electrode material according to claim 6, characterized in that: The manganese source is selected from one or more combinations of metallic manganese, manganese monoxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese citrate, manganese acetate, manganese oxalate, manganese sulfate, manganese nitrate, and manganese chloride; The nickel source is selected from one or more combinations of nickel metal, nickel hydroxide, nickel sulfate, nickel oxalate, nickel carbonate, nickel nitrate, and nickel chloride; The lithium source is selected from one or more combinations of lithium carbonate, lithium bicarbonate, lithium sulfate, lithium phosphate, lithium oxalate and lithium hydroxide; The phosphorus source is selected from a combination of one or more of ammonium phosphate, lithium phosphate, sodium phosphate, phosphoric acid, and hypophosphorous acid; The raw material of the doping element M is selected from one or more combinations of sulfates, phosphates, nitrates, chlorides, oxalates, acetates, and carbonates of any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg; The carbon source is selected from one or more combinations of organic carbon, artificial or natural graphite, graphene, carbon nanotubes or Super P, acetylene black or other conductive carbons.
8. A method for preparing a 5V high voltage positive electrode material, characterized in that: The soluble manganese source, nickel source and phosphorus source are fully dissolved and filtered according to the stoichiometric ratio to obtain a clean solution, and a hydrothermal reaction is carried out in a hydrothermal kettle at a certain pressure and temperature. After a period of hydrothermal reaction, the material is filtered to obtain a filter cake, and the filter cake is dried and sintered to obtain a nickel manganese phosphate active material with an olivine structure. The hydrothermal reaction temperature is 60-500° C. and the hydrothermal reaction pressure is 1-20 MPa. Alternatively, a soluble manganese source, a nickel source, a lithium source, a phosphorus source, a carbon source and doping elements are fully dissolved and filtered according to a stoichiometric ratio to obtain a clean solution, and a hydrothermal reaction is carried out in a hydrothermal kettle at a certain pressure and temperature. After a period of hydrothermal reaction, the material is filtered to obtain a filter cake, and the filter cake is dried and sintered to obtain a carbon-coated nickel manganese phosphate active material with an olivine structure. The hydrothermal reaction temperature is 60-500° C. and the hydrothermal reaction pressure is 1-20 MPa. Nickel manganese phosphate active material with olivine structure, the general structural formula is Ni b Mn d M e PO4, wherein b is 0.8, d is 0.2, and e is 0≤e≤0.5; or b is 0.7, d is 0.3, and e is 0≤e≤0.5; or b is 0.6, d is 0.4, and e is 0≤e≤0.5; or b is 0.5, d is 0.5, and e is 0≤e≤0.5; M is a doping element, and M is selected from one or more combinations of Fe, Al, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, Mg, N, or S.
9. The method for preparing a 5V high voltage positive electrode material according to claim 8, characterized in that: After the hydrothermal reaction, the product is dried, and a carbon source and a lithium source are added so that Li a Ni b Mn d M e PO4 / C, the molar amount of lithium is 0.01-1.05, the carbon content is 0.1-10%, the solid-liquid ratio is adjusted to 40-45%, the viscosity is controlled at 4000-5000 Pa·s, and the particle size D50 is ground to 200-800 nm and then spray-dried; The sintering temperature is 400-600°C, more preferably 450°C-500°C.
10. The method for preparing a 5V high voltage positive electrode material according to claim 9, characterized in that: The manganese source is selected from one or more combinations of metallic manganese, manganese monoxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese citrate, manganese acetate, manganese oxalate, manganese sulfate, manganese nitrate, and manganese chloride; The nickel source is selected from one or more combinations of nickel metal, nickel hydroxide, nickel sulfate, nickel oxalate, nickel carbonate, nickel nitrate, and nickel chloride; The lithium source is selected from one or more combinations of lithium carbonate, lithium bicarbonate, lithium sulfate, lithium phosphate, lithium oxalate and lithium hydroxide; The phosphorus source is selected from a combination of one or more of ammonium phosphate, lithium phosphate, sodium phosphate, phosphoric acid, and hypophosphorous acid; The raw material of the doping element M is selected from one or more combinations of sulfates, phosphates, nitrates, chlorides, oxalates, acetates, and carbonates of any one of Fe, Co, Ca, Pb, Na, Ti, Zr, Mo, V, Nb, Sc, Cr, Cu, Zn, Be, La, and Mg; The carbon source is selected from one or more combinations of organic carbon, artificial or natural graphite, graphene, carbon nanotubes or Super P, acetylene black or other conductive carbons.
11. The method for preparing a 5V high voltage positive electrode material according to any one of claims 1 to 10, characterized in that: A nickel manganese phosphate positive electrode material or a carbon-coated nickel manganese phosphate positive electrode material is prepared by the method described in any one of claims 1 to 10. The active material has a 5V high voltage platform as a phosphate positive electrode material.
12. The method for preparing a 5V high voltage positive electrode material according to any one of claim 11, characterized in that: A 5V high-voltage lithium battery pole piece, comprising a battery pole piece made of the positive electrode material, i.e. a carbon-coated nickel manganese lithium phosphate composite positive electrode material pole piece, wherein the positive electrode material component contains 1-100wt% of carbon-coated nickel manganese lithium phosphate positive electrode material, preferably the positive electrode material component contains 1-90wt% of carbon-coated nickel manganese lithium phosphate positive electrode material, preferably the positive electrode material component contains 10-80wt% of carbon-coated nickel manganese lithium phosphate positive electrode material, preferably the positive electrode material component contains 20-70wt% of carbon-coated nickel manganese lithium phosphate positive electrode material, preferably the positive electrode material component contains 30-70wt% of carbon-coated nickel manganese lithium phosphate positive electrode material, preferably the positive electrode material component contains 30-60wt% of carbon-coated nickel manganese lithium phosphate positive electrode material.
13. The method for preparing a 5V high voltage positive electrode material according to claim 12, characterized in that: When the carbon-coated nickel manganese lithium phosphate positive electrode material is less than 100%, it also contains other positive electrode materials, and the other positive electrode materials are selected from any one of lithium cobalt oxide, lithium manganese oxide, nickel cobalt aluminum ternary polymer material, nickel cobalt manganese ternary polymer material, and nickel manganese phosphate active material with an olivine structure; the structural formula of the nickel manganese phosphate active material with an olivine structure is selected from any one of the methods prepared in claims 1-10.
Citation Information
Patent Citations
Lithium manganese iron phosphate type material and preparation method therefor, battery paste, positive electrode, and lithium battery
CN106935851A
Graphene in-situ composite iron manganese nickel lithium phosphate positive electrode material and preparation method thereof
CN108288708A
Preparation method of precursor and lithium iron nickel phosphate positive electrode material
CN114105117A
Spherical lithium ferric manganese phosphate nanoparticles and preparation method thereof
CN115974036A